Synthesis, characterisation and investigation of enhanced photocatalytic activity of Sm+3, Ni+2 co-doped TiO2 nanoparticles on the degradation of azo dyes in visible region. (2019) - Bashir, Amna; Bashir, Fatima; Mehmood, Zahid; Satti, Muhammad Sultan; Akhter, Zareen
Pure and samarium-nickel co-doped TiO2 nanoparticles with different Sm contents were synthesised by sol-gel method. The synthesised nanoparticles were characterised using different techniques. It is revealed from experimental results that the doping of TiO2 with samarium and nickel not only increase the surface area of mesoporous TiO2 but also decrease the particle size (17.0 nm to 8.01 nm by increasing Sm +3 contents). Diffuse-reflectance spectroscopic studies showed the slight red shift in band-gap transitions and appearance of the new absorption band in the visible region (719 nm) caused by Ni +2 and Sm +3 doping. The photocatalytic degradation of azo dyes (Reactive Red-195 and Reactive Black-08) was carried out in visible region using modified TiO2 at different pH values. Results revealed that 99% of RR-195 and 75.33% RB-08 were degraded after 10-20 minutes of irradiation. Maximum degradation was achieved in case of nanoparticles co-doped with 5% Ni and 3% Sm.